TajdÃ®d al-Nahwi ’Inda TammÃ¢m HassÃ¢n wa Atsaruhu bi MÃ¢ddati Ta’lÃ®mi al-Nahwi li Ghairi al-NÃ¢thiqÃ®na bi al-Lughah al-’Arabiyyah - Bani Muhtarom, Muslihudin; Bani Hafidah, Hafidah (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2023)
Nahwu science now contains philosophy so it is difficult to learn. In addition, the science of nahwu compiled by classical scholars reduces it to one qorinah or guidance, namely I’rob. In fact, most words in Arabic end with the letter ’Ilat which cannot be identified with I’rob. The aims of this research are twofold, namely (1) to explain the new theory in nahwu science which was carried out by Tammam Hassan. (2) explain its effect on nahwu learning materials for non-Arabic speakers. This research is the qualitative research, the type of research is library research. The result of this research is to offer Tammam Hassan’s renewal of nahwu (tajdid al-nahwi), namely Qarain al-Lafdziyah. Its influence makes al-kalimat divided into seven, including: al-ism, al-washfi, al-fi’li, al-dhomir, al-dzorof, al-kholifat, and al-’adat. The era is divided into two, namely the al-Nahwi era and the al-Shorfi era. With these qarain (instructions), it greatly influences the broader and more understanding nahwu learning material . Therefore, it is very necessary for researchers, educators, and students to explore the renewal of nahwu knowledge in depth.